2010
DOI: 10.1183/09031936.00125809
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor signalling contributes to house dust mite-induced epithelial barrier dysfunction

Abstract: Impaired airway epithelial barrier function has emerged as a key factor in the pathogenesis of allergic asthma. We aimed to discern the involvement of the epidermal growth factor receptor (EGFR) in allergen-induced epithelial barrier impairment, as we previously observed that house dust mite (HDM) signals through EGFR.We investigated the junctional integrity of human bronchial epithelial cells using electric cellsubstrate impedance sensing and immunofluorescent staining.HDM induced a rapid, transient fall in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
71
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 40 publications
7
71
0
Order By: Relevance
“…reduced HDM-triggered decreases in epithelial resistance and improved restoration of epithelial junctions (21). Similarly, EGFR inhibition increased epithelial barrier recovery upon electroporation-induced injury (21).…”
Section: Egf Receptor (Egfr) Activation In Lungs Of Mice Treated Withmentioning
confidence: 99%
“…reduced HDM-triggered decreases in epithelial resistance and improved restoration of epithelial junctions (21). Similarly, EGFR inhibition increased epithelial barrier recovery upon electroporation-induced injury (21).…”
Section: Egf Receptor (Egfr) Activation In Lungs Of Mice Treated Withmentioning
confidence: 99%
“…This would not have been detected in our design, where the longest duration of observation was 2 h after a single instillation. However, in vitro, near maximal effects were observed after only 15-30 min of exposure (8,25). Moreover, a design with repeated exposure over several days would not have been feasible to address our hypothesis.…”
Section: Discussionmentioning
confidence: 89%
“…Further support was obtained in studies of direct exposure of cultured epithelial cells to HDM fecal pellets or extract. Wan and colleagues (25) observed a time-dependent decrease in barrier function, which peaked at ϳ2 h and was still present at 6 h, whereas Heijink et al (8) observed decreased transepithelial resistance at 15 min which had resolved by 60 min. The fact that we did not observe any in vivo effect of direct exposure to HDM on either barrier function or responsiveness to MCh after either 30 min or 2 h suggests that any such effect must be minor and would seem unlikely to play a significant role in severity of disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations